Kondisi Kualitas Air Danau Toba di Kecamatan Haranggaol Horison Kabupaten Simalungun Sumatera Utara - Debi Debora Haro; Yunasfi Djayus; Zulham Apandy Harahap (AQUACOASTMARINE, 2013)
Aquaculture of floating net cages system at Lake Toba in particularHaranggaol developed rapidly, As uncontrolled development unit ofculture can cause water quality decreased in Haranggaol, Toba Lake sothat it can pass through water quality standard. This research aim to knowthe level of water pollution in Lake Toba Haranggaol using the STORETand Index Pollution Method then compare it without floating net cages.This research was done in May- July 2013. Sampling method used methodof purposive random sampling. Station was used for research was Station 1at environment of floating net cages and Station 2 at without floating netcages area. Result shown water temperature: 26-28 0C, brightness: 2,8-5,35meter, turbidity: 0,16-7.13 NTU, TSS: 12.36-19.36 mg/l, pH: 7,1-8,3, DO:4,3–6,3 mg/l, BOD: 0,4-1,7 mg/l, COD: 4,42-6,63 mg/l, NH3: 0,115-0,293mg/l, NO3: 0,306-0,814 mg/l, NO2: 0,001-0,015 mg/l, PO4: 0,038-0,188mg/land Colifecal: 8,6–22,2 MPN/100 ml. Based on the results of research therewere some parameters that have passed water quality standard atenvironment of floating net cages was 0,217 mg/l of NH3, 0,578 mg/l of NO3and 0,134 mg/l of PO4, while at without floating net cages area was 0,144mg/l of NH3, 0,401 mg/l of NO3 and 0,056 mg/l of PO4. Based on Storetmethod, both research station categorized into the class C that was middlepolluted. While according to Pollution Index method both research stationcategorized light polluted to middle polluted.`Key words: Colifecal, Floating Net Cages, Water Quality